ON THE ISSUE OF PREPARING THE FUTURE MEDICAL SPECIALISTS - Denysenko, O.V.; Fomina, I.L. (Pedagogy of Higher and Secondary Education, 2006)
Different aspects of activating o f future professional activity of student-medicians are discussed.